Children's spaces - Dudek, Mark (Elsevier/Architectural Press, 2005)
This collection of essays is concerned with the experiences children have within the supervised worlds they inhabit, as well as with architecture and landscape architecture. International examples of innovative childcare practice are illustrated together with the design processes which informed their development. The emphasis here is on new and experimental childcare projects which set-out to reassert the rights of children to participate in a complex multi-faceted world, which is no longer available to them, unless under adult supervision. Research supports in depth recommendations regarding t.